Reflective practice in nursing - Bulman, Chris, ....-; Schutz, Sue., ....- (Hoboken : Wiley-Blackwell, 2013)
The ability to reflect on practice has become a competency demanded of every healthcare professional in recent years. It can be a daunting prospect- but this practical and accessible text guides the way, using the latest research and evidence to support the development of skills in reflective practice and provides help and advice on how to get started, how to write reflectively and how to continue to use reflective practice in everyday situations. This fifth edition of Reflective Practice in Nursing is a guide for students and practitioners alike who wish to learn more about reflective practice, as well as containing essential information for teachers and lecturers.
An introduction to reflection / Chris Bulman -- Developing skills for reflective practice / Sue Atkins and Sue Schutz -- Writing to learn : writing reflectively / Sylvina Tate -- Reflecting in groups / Bernadette Carter -- An exploration of the student and mentor journey into reflective practice / Charlotte Maddison and Pam Sharp -- Supervision for supervisors : icing on the cake or a basic ingredient for the development of clinical supervision in nursing? / John Driscoll and Paul Cassedy -- A personal exploration of reflection and clinical expertise / Sue Duke -- Assessing and evaluating reflection / Sue Schutz -- Getting started on a journey with reflection / Chris Bulman.
Includes bibliographical references and index.
Keywords: Education, Nursing; Learning; Nursing Process; Nursing; Philosophy, Nursing; Reflecteren; Thinking; Verpleegkunde